El miedo a la revolución y los “deberes del patriotismo”: el debate Acosta-Riera Aguinagalde frente a la guerra federal en Venezuela, 1859-1863 - Reinaldo Rojas (Centre de Recherches sur les Mondes Américains, 2007)
The hardness in the armed struggle that defined the Federal war in Venezuela, country men war against large landed estate, from liberals against “godos” and poor against rich ones, is doubtless the hardest moment in social violence that occured almost all XIX century long and transformed that event in a real “fabrique d’emotions”, whose effects in venezuelan mind has been treated by positivist historians like Lisandro Alvarado and Laureano Vallenilla Lanz in accordance with social equality thesis. Besides this historiographic work about the political effects of that warlike event, the study of the debate made in 1867 and 1868 between these two great thinkers from that time, “Don” Cecilio Acosta and Dr. Ildefonso Riera Aguinagalde, about the justice and necessity of that social war, can give us the keys about the sensibility level of that society which assumed the notion of revolution, appearing in the venezuelan political vocabulary as a representation of the necessity of social change related to the progress, justice and freedom idea, which was only possible through violence way. The purpose of this communication is to contextualize that debate, either in its social element or in the symbolic universe in which the sensibility to change and its mediation through the liberal political discourse is introduced.